Comprehensive technical risk indices and advanced methodologies for power system risk management - Yaghoubi, Elaheh; Yaghoubi, Elnaz; Maghami, Mohammad Reza; Jahromi, Mehdi Zareian (Electric power systems research, 2025)
•Rising complexity in power systems demands a shift to accurate risk assessment for reliable electricity.•Despite recent studies, the true impact of risk analysis on power systems remains unclear.•Existing research focuses on specific risk metrics, neglecting the evolving landscape of risk analysis practices.•This review delves into all risk measurement methods, providing a comprehensive understanding of power system risk management.•The review identifies under-utilized indices (EUE, LOLP, etc.), advocates for cost & time inclusion, and promotes FMEA for its strengths in uncertainty & reliability analysis. In a dynamic and complex power system landscape, accurately assessing and mitigating technical risks is essential for ensuring a reliable and secure electricity supply. Despite advancement, significant research gaps persist in understanding the broader trends of risk analysis and exploring comprehensive technical risk indices. Existing studies often focus narrowly on specific measures, overlooking evolving dynamics in power systems risk management. This review addresses these gaps by systematically examining a range of risk measures, including underexplored indices such as loss of load expectation (LOLE), expected unserved energy (EUE), load ability limits (LAL), and energy expected not served (EENS), alongside commonly studied indices like voltage devotion and resilience. The review systematically addresses this challenge through three sections, ensuring a logical progression from introduction to analysis and findings. LOLE estimates the likelihood of power supply shortages, while EUE quantifies the expected energy not delivered due to outages. Additionally, underexplored metrics LAL and EENS analysis provide a more holistic view of system vulnerabilities. The study employs systematic reviews with bibliometrics analysis to identify key challenges, analyze academic research trends, and introduce methodologies, like failure mode and effects analysis (FMEA). FMEA identifies potential failure points, assesses their impacts, and integrates uncertainty and reliability into risk analysis, offering valuable insights into power system vulnerabilities. This approach ensures a detailed understanding of vulnerability, allowing for proactive measures in system reliability. The review is structured into three sections: an introduction to common technical risk indices, an exploration of challenges in current risk management, and an assessment of novel methodologies and their practical implications. Findings emphasize that indices like LOLE and EUE receive less attention compared to metrics like resilience and uncertainty. Furthermore, cost and time considerations in risk evaluation remain underexplored. This paper offers actionable insights for power companies to optimize operational planning and prioritize investments and enhance system reliability. Integrating underutilized indices with innovative methods like FMEA, this article provides a novel risk analysis framework that bridges theoretical gaps and supports practical decision-making. [Display omitted]